Errors in corticospinal axon guidance in mice lacking the neural cell adhesion molecule L1. - Cohen, N; Taylor, J; Scott, L; Guillery, R; Soriano, P; Furley, A (1998)
BACKGROUND: Neural cell adhesion molecules of the immunoglobulin superfamily (IgCAMs) have been implicated in both the fasciculation and guidance of axons, but direct genetic evidence of a role for neural IgCAMs in axon guidance in vertebrates is lacking. The L1 subfamily of vertebrate neural IgCAMs function as both homophilic and heterophilic receptors for a variety of cell-surface and extracellular ligands and may signal through intracellular kinases or by recruitment of the fibroblast growth factor receptor. L1 itself has been implicated in many neural processes and is expressed widely in the embryonic and adult nervous systems. In humans, mutations in the L1 gene are linked with a spectrum of brain disorders, including loss of the corticospinal tract, but the mechanistic basis for these disorders is unknown. RESULTS: We show that mice that do not express L1 have defects in the guidance of axons of the corticospinal tract, a major motor control pathway projecting from the cortex to the spinal cord. Although the pathway to the caudal medulla appears normal, a substantial proportion of axons fail to cross the midline to the opposite dorsal column as normal. In adults, this results in a reduced decussation and in large numbers of axons projecting ipsilaterally. There is also a varying, but reduced, number of corticospinal axons in the dorsal columns of the spinal cord. These do not project beyond cervical levels. We show that these are defects in axon guidance, because they arise during the early stages of the development of the decussation. The presence of a ligand for L1, CD24, specifically at the point of decussation suggests a mechanism in which L1 functions to guide corticospinal axons across the midline. CONCLUSIONS: L1 function is necessary for the guidance of corticospinal axons across the pyramidal decussation in mice. Some of the defects in the corticospinal tract of humans with mutations in L1 could be due to errors in axon guidance at the pyramidal decussation.